Effects of high vs. low cadence training on cyclists` brain cortical activity during exercise - Ludyga, S.; Gronwald, T.; Hottenrott, K. (Journal of Science and Medicine in Sport, 2016)
Objectives: As brain cortical activity depends on cadence, exercise at different pedaling frequencies could provide efficient stimuli for functional adaptations of the brain. Therefore, the purpose of the study was to investigate the effects of cadence-specific training on brain cortical activity as well as endurance performance. Design: Randomized, controlled experimental trial in a repeated measure design. Methods: Male (n = 24) and female (n = 12) cyclists were randomly assigned to either a high cadence group (HCT), a low cadence group (LCT) or a control group (CON) for a 4 week intervention period. All groups performed 4 h of basic endurance training per week. Additionally, HCT and LCT completed four cadence-specific 60 min sessions weekly. At baseline and after 4 weeks subjects performed an incremental test with spirometry as well as an interval session (constant load; varying cadences) with continuous recording of electroencephalographic (EEG) rhythms. Results: In contrast to CON, HCT and LCT elicited similar improvements of maximal oxygen uptake and power at the individual anaerobic threshold. Additionally, there was a reduction of alpha-, beta- and overall-power spectral density in HCT, which was more pronounced at high cadences. Improvements of endurance performance were correlated with reductions of EEG spectral power at 90 and 120 rpm. Conclusions: Whereas high and low cadence training elicit similar improvements in endurance performance, brain cortical activity is especially sensitive to high cadence training. Its reduction can be interpreted in the sense of the neural efficiency hypothesis and might as well influence the sensation of central fatigue positively.